The Role of Radiotherapy in Soft Tissue Sarcoma on Extremities With Lymph Nodes Metastasis: An IPTW Propensity Score Analysis of the SEER Database - Qiu, Xinzhu; He, Hongbo; Zeng, Hao; Tong, Xiaopeng; Liu, Qing (Frontiers in Oncology, 2021)
Background Soft tissue sarcomas on extremities with regional lymph nodes metastasis (STSE-RLNM) is a devastating situation. Optimizing therapeutic approaches is vital but hampered by a shortage of randomized trials. We used a population-level database to evaluate radiotherapy’s impact on sarcoma-specific survival (SSS) and overall survival (OS) for surgery for STSE-RLNM. Methods We retrospectively screened data from the SEER database (2004–2015), and 265 patients with STSE-RLNM who received surgery, with (134) or without (131) radiotherapy, were enrolled in this study. A propensity-score-matched analysis with the inverse probability of treatment weighting (IPTW) Kaplan–Meier curve was created. The log-rank test and Cox regression analysis were performed to compare SSS and OS in patients with and without radiotherapy. Further analysis of radiotherapy time was conducted, and the Kaplan–Meier curve and the log-rank test were done. Landmark analysis was introduced to attenuate the immortal bias. Results In the original unadjusted cohort, the radiotherapy + surgery group is associated with improved SSS [hazard ratio (HR), 0.66; 95% CI, 0.47–0.91; p = 0.011] and OS (HR, 0.64; 95% CI, 0.47–0.88; p = 0.006). This significant treatment effect was also noted in IPTW-adjusted Cox regression either on SSS (HR, 0.65; 95% CI, 0.45–0.93; p = 0.020) or on OS (HR, 0.64; 95% CI, 0.46–0.91; p = 0.013). The Kaplan–Meier curve and log-rank test showed that pre- and postoperative radiotherapy was not related to SSS (p = 0.980 or OS (p = 0.890). Conclusion Radiotherapy and surgery has a significant benefit on the prognosis of patients with STSE-RLNM compared to surgery alone. These findings should be considered when making treatment decisions for them.